Spatio-temporal variability of the trophic ecology of the cockle (Cerastoderma edule) in an estuarine bay : - Varin, Laura (2014)
Estuaries are located at the interface between oceans and rivers. These ecosystems aresubmitted to spatio-temporal variations of environmental parameters which can affect benthiccommunities. Seasonally, during three years, cockles (Cerastoderma edule) were collectedfrom three stations in the Baie des Veys (Normandy, France). Their isotopic compositionswere observed in function of several factors (year, season, station and size class) andcombined with their potential food sources [i.e. particulate organic matter (POM), riverineparticulate organic matter (RPOM) and microphytobenthos (MPB)]. Stable isotope analysis,based on a set of carbon and nitrogen ratios, was applied to assess differences in cockles’ diet.Permutation analysis of variance (PERMANOVA) was used to test the effects of factors onthe cockles’ flesh composition and food sources were investigated using a stable isotopemixing model (SIAR). Results showcase no differences about δ13C and δ15N ratios betweenjuveniles and adults neither differences between stations and between years. In contrast, ameasurable effect of season on cockles’ isotopic composition (p<0.001) as well as asignificant interaction between season and year was highlighted. The seasonal differences ofstable carbon isotope ratios in cockles result from variability of food intakes. RPOM isconsidered like an alternative food source because it did not contribute enough to the cockles’diet unlike POM and MPB. Food sources contributions showed that MPB is preferentiallyconsumed because, on average, 60% of cockle production originated from MPB during thestudy period. There is an inter-annual variation of isotopic signatures of individuals probablycaused by physiological responses to variations of environmental parameters. Seasons aredifferent (temperature, luminosity, pluviometry), affect sources' signature and consequentlycockles' signature vary also.